Understanding management practices and user’s perspective on sustainable forest management in Nepal - Ghimire, Pramod; Magar, Lilu Kumari; Lamichhane, Uchita; Ghimire, Keshav; Gaire, Pitamber (Journal of Forests, 2025)
Sustainable forest management (SFM) plays a critical role in maintaining ecological balance, supporting livelihoods, and mitigating climate change. This study was conducted to explore the management practices and user perspectives regarding sustainable forest management in Nepal, focusing on community forestry and government-led initiatives. Using a mixed-methods approach, data were collected through surveys, interviews, focus group discussions and field observations. A total of 180 user’s opinion were collected in 9 selected forest user groups from four district of Nepal (i.e. Ilam, Jhapa, Sarlahi, and Makawanpur). The study revealed that major forest management practices applied by community users’ are thinning, pruning, and improvement felling. Majority of the users (70.56%) were unsure about the forest management practices prescribed in the Operational plans (OPs). Accordingly, most users (92.78%) were agreed with the opinions that they need to be trained about forest management practices and its implementation. Majority of the users (92.00%) also agreed that participatory forest management modalities like Community Forest (CF), Collaborative Forest Management (CFM) and Leasehold Forest (LHF) area protecting biodiversity and reducing environmental risks. However, people believe that arbitrary policy changes was the main challenges for proper implementation of sustainable forest management practices. Therefore, strengthening capacity-building programs, enhancing government support, developing a consistent guideline, and promoting adaptive management practices are essential for improving sustainable forest resource management in Nepal.